Skeletal evidence of Diffuse Idiopathic Skeletal Hyperostosis (DISH) in a collective burial from Byzantine Greece - Tritsaroli, Paraskevi (Anthropological Review, 2018)
The paper reports on a collective burial from a 13th c. AD cist grave in Attica, Greece. The grave was located inside a basilica and held the remains of at least ten adults. Bone representation analysis showed secondary manipulation of previous deceased including long bone selection for reburial in the same grave and/or bones transported from a different burial place. Paleopathological analysis used macroscopy and radiology, and revealed several lesions on the axial and appendicular skeleton expressed mainly by spinal ligament ossification and multiple peripheral enthesopathies. Individuation of the remains pointed to a middle-aged male with DISH, a condition often correlated to high social rank. Byzantine period is marked by increasing development and prosperity in Greece including among others the creation of many local monastic centers. Although the precise social and professional profile of these individuals cannot be revealed, the combined investigation of skeletal and archaeological evidence suggests that the grave gathered the remains of individuals belonging to an upper class social group.